Joint-less walking robot - Ong, Chong Chin. (2009)
This report presents the research done on a continuum type robotic arm which is realized by a 300mm long and 100mm diameter helical compression spring. Initially, the investigation is directed towards a jumping mechanism. After that, the idea was rejected due to the difficulty to balance the whole robot and the lack of inertia to propel the whole robot. The project was directed to a walking robot which utilized the spring as continuum type robotic arm to pedal the whole robot. This project concerns the design of the robot which includes the design of the hardware and sortware for the moving mechanism, fabrication of the hardware and experiments to analyze the accuracy and repeatability of the movement of the robot. The robot design in this project uses three aluminum legs with caster wheels at the end as the support for the robot. Three servo motors are used to actuate cable drums connected to the spring. This creates a bending moment and in turn a ‘pedaling’ action. The direction of movement of the robot is controlled by manipulating the orientation of the spring bending moment. The result of the experiment of the movement is analyzed to determine whether continuum type robotic arm is applicable in more advanced robots.